Diagnostic approach to splenic lesions - Krähling, Hermann; Seidensticker, Max; Heindel, Walter L.; Gerwing, Mirjam (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2023)
Background Splenic lesions are rare and mostly incidental findings on cross-sectional imaging. Most lesions are of benign nature and can be correctly identified based on imaging characteristics. Further, invasive evaluation is only necessary in cases of splenic lesions with uncertain or potentially malignant etiology.Method While in most cases a correct diagnosis can be made from computed tomography (CT), (additional) magnetic resonance imaging (MRI) can aid in the identification of lesions. As these lesions are rare, only a few of the differential diagnoses are regularly diagnosed in the clinical routine.Result and Conclusion This review presents the differential diagnoses of splenic lesions, including imaging characteristics and a flowchart to determine the right diagnosis. In conjunction with laboratory results and clinical symptoms, histological workup is necessary only in a few cases, especially in incidental findings. In these cases, image-guided biopsies should be preferred over splenectomy, if possible.Key Points Citation Format
Keywords: spleen; diagnostic radiology; CT; MR-imaging